Pregled zdravilnih učinkovin za zdravljenje anksioznosti - Anderluh, Marko (Farmacevtski vestnik, 2010)
The prevalence of all anxiety disorders makes them one of the most frequent mental disorders along with depressive disorders. The treatment of anxiety disorders consists of cognitive-behavioral therapy and pharmacotherapy with antidepressants and anxiolytics. The article presented deals with classification of anxiety disorders, treatment methods and the review of anxiolytics.
Keywords: anksiolitiki; anksioznost; farmakoterapija; mehanizem delovanja